Economic efficiency, energy consumption and sustainable development - Bojnec, Štefan; Papler, Drago (Journal of Business Economics and Management, 2011)
This paper analyzes structural indicators of economic efficiency and energy intensity consumption as determinants of sustainable economic development for the selected 33 European countries. The correlation, regression and multivariate factor analyses are applied to test the associations between the selected structural variables of energy intensity consumption, economic efficiency, and the main driving forces behind these developments. Economic efficiency is positively associated with expenditures on research and development (R&D) and a greater technological intensity of exports, while at the same time the economic efficiency of R&D expenditures and technological intensity of exports reduce the energy intensity consumption of the economy. The results suggest that management strategies and policies directed towards R&D expenditures, human capital investments, and technologically intensive export oriented products are improving economic efficiency performance and contributing to energy saving sustainable economic development. The technological intensity of products reduces energy consumption, which is related to restructuring of energy intensive industries into more advanced and energy saving ones with higher value added per unit of product, but with lower energy consumption per unit of product.Article in English.Ekonominis efektyvumas, energijos vartojimas ir subalansuota plėtraSantrauka. Autoriai analizuoja struktūrinius ekonominio efektyvumo ir energijos vartojimo intensyvumo, kaip vienų iš pagrindinių subalansuotos plėtros kintamųjų, rodiklius. Tirti buvo pasirinktos 33 Europos valstybės. Autoriai, siekdami pagrįsti iškeltus teiginius, naudojo koreliacinę, regresinę analizę bei daugiakriterinius metodus galimoms ekonominio efektyvumo bei energijos vartojimo laipsnio (ir kitų, ne mažiau svarbių elementų) variacijoms nustatyti. Ekonominis efektyvumas labai dažnai asocijuojasi su tyrimais ir plėtra (R&D), eksportuojamomis aukštosiomis technologijomis. Remdamiesi atliktų tyrimų rezultatais autoriai siūlo nukreipti tiek politinius sprendimus, tiek valdymo strategijas į tyrimų ir plėtros (R&D) veiklas, investicijas į žmogiškuosius išteklius, technologinius sprendimus, nes visa tai galima susieti su subalansuotos plėtros koncepcija.Reikšminiai žodžiai: ekonominis efektyvumas, energijos vartojimas, tyrimai ir plėtra, technologinis intensyvumas, subalansuota plėtra, Europa.